(untitled) (Journal of Namibian Studies : History Politics Culture, 2023)
Sustainable development is of utmost importance in recent years because of several environmental and economic concerns which threatens the existence of living things in this ecosystem. However, the Higher Education Institutes (HEIs) are one of the prime components which can trigger sustainable behaviors among the younger generations which can effectively minimize the menaces towards sustainable development. In this research study, a comprehensive questionnaire was designed in order to evaluate the perceptions of the Japanese as well as international students about BRs and different aspects of SDGs No: 8 (Decent Work and Economic Growth), 12 (Responsible Consumption and Production), 13 (Climate Action), 14 (Life Below Water) and 15 (Life on Land). The students from different universities of Japan, India, Sri Lanka, and Africa were recruited for an online training program where they were introduced to BRs which are UNESCO designated places for the promotion and preservation of sustainable behaviors and activities. The evaluation of the behaviors or perceptions of the students was carried out in two phase system; pre-evaluation and post-evaluation which was conducted before the start of the online training program and after the program. The students were awarded with certificates as a token of appreciation upon the successful completion of the training programs. The results of the statistical evaluation confirm that there was statistically significant difference between the evaluation of the students throughout the training programs. The results imply that the understanding of the international students is more towards sustainable development and behavioral learning as compared to their counterparts. The females more tend to work at higher salaries even if the working environment is not feasible. In addition, some of the core challenges are also identified which hinder the sustainable development in the behavioral learning of students at higher education institutes. It has been inferred that HEIs can utilize UNESCO designated BRs as learning platforms with innovation in curriculum design, teaching, research, and training. Finally, some of the practical implications are proposed for promoting sustainable behaviors and autonomy comprehension of SDGs among students at HEIs via using BRs as learning places to meet the present and future challenges posed for sustainable development.